2013
DOI: 10.1137/120883050
|View full text |Cite
|
Sign up to set email alerts
|

Structured Low-Rank Approximation with Missing Data

Abstract: We consider low-rank approximation of affinely structured matrices with missing elements. The method proposed is based on reformulation of the problem as inner and outer optimization. The inner minimization is a singular linear least-norm problem and admits an analytic solution. The outer problem is a nonlinear least squares problem and is solved by local optimization methods: minimization subject to quadratic equality constraints and unconstrained minimization with regularized cost function. The method is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 20 publications
1
80
0
Order By: Relevance
“…Fast methods for evaluation of f and its derivatives are presented in [39] and implemented in C++. The general case is a generalized least norm problem and is solved in [23].…”
Section: Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast methods for evaluation of f and its derivatives are presented in [39] and implemented in C++. The general case is a generalized least norm problem and is solved in [23].…”
Section: Solution Methodsmentioning
confidence: 99%
“…The software is written in C++ with Matlab/Octave and R interfaces and contains also the experimental Matlab code, presented in [23]. The latter supports general linear structure and missing values, but is inefficient and can be used only for small size matrices (say, m ≤ n < 100).…”
Section: Interfaces To Scientific Computing Environmentsmentioning
confidence: 99%
“…In [11], it is sown how this problem can be solved in the presence of exact (v i = +∞) and missing (v i = 0) values. In [12], it is shown that fast O(T ) evaluation of M and its derivatives can be performed for mosaic-Hankel-like structured matrices.…”
Section: Solution Methodsmentioning
confidence: 99%
“…In total, 215 samples are missing in a periodic pattern, see Figure 1. The precise simulation parameters are specified in the following fragment of the m-file reproducing the presented numerical results: example +≡ (1,6), [], -1); T = 500; n = 6; w0 = initial(ss(sys0), ones(n, 1), T -1); Tm = sort(unique([1:7:T, 3:7:T, 5:7:T])); w = w0; w(Tm) = NaN; Two identification methods, described in the paper, are applied on the data and the results are validated by the distance between the characteristic polynomials of the true and identified models: example +≡ dist = @(sys1, sys2) norm(poly(eig(sys1))...…”
Section: Motivating Examplementioning
confidence: 99%
“…• methods based on convex relaxations [3], and • methods based on local optimization [4], [5], [6], [7]. To the best of our knowledge, the class of the subspace methods [8] has not been extended to deal with missing data.…”
Section: Introductionmentioning
confidence: 99%